Information Dissemination and the Monetary Policy Uncertainty Premium: Evidence from China - Lin, Jianhao; Fan, Jiacheng; Zhang, Yifan (Journal of Banking & Finance, 2025)
This paper proposes a novel monetary policy uncertainty (MPU) measure aggregating information from policy communication, policy operation and news coverage. We find that the aggregate MPU measure significantly commands a negative risk premium in the cross-section of the Chinese stock market. Stocks with higher (lower) MPU beta, favored (avoided) for hedging against MPU shocks, contribute to the premium through their under-performance (outperformance). Our results remain robust after controlling for economic uncertainty, economic policy uncertainty, and monetary policy surprises. We further show that the aggregate MPU measure outperforms its individual components in both portfolio- and stock-level asset pricing tests.